The collection of household organic waste for the control of synanthropic vector-borne diseases in the municipality of Ipixuna do Pará, northeast Pará (Research, Society and Development, 2021)
The collection of organic waste is important to ensure the welfare of the community, when this service does not occur or is done improperly, it triggers a series of problems to the population and the environment. The objective of this research was to perform a qualitative and quantitative analysis of the influence of garbage in the proliferation of vectors that cause pathologies that aggravate public health. For this, the comparative method was used, with a quantitative and qualitative approach. The primary data was obtained in situ. To obtain secondary data, a survey of documental data was carried out using open access links, such as the periodical portal of the Coordination for Higher Education Research (CAPES) and the Scientific Electronic Library Online (SciELO), and the time frame was limited to 2008 and 2020. The data obtained and analyzed indicated that: (1) garbage collection is efficient when it comes to a neighborhood near major commercial points, but in peripheral neighborhoods these services are precarious; (2) there is the accumulation of garbage in inappropriate places and considerably influences the appearance of vectors. It is concluded that there is a lack of awareness of the population, with respect to garbage, since many residents even having collection from Monday to Friday, promote final disposal of garbage in inappropriate places; another fact is the inadequate packaging, i.e., in plastic bags, when disposed of the municipal collection, which can easily be torn by animals and thus attract vectors more easily, which increases the spread of diseases in the community.